Reporting of Progress toward Eliminating Viral Hepatitis B and C in the Central Asian Region - Bibinur Nurmanova (Advanced Gut & Microbiome Research)
Eliminating viral hepatitis became a global goal and was targeted by countries worldwide. Using WHO, Google Scholar, PubMed, and other databases, the progress of Central Asian countries (Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan) in ending viral hepatitis B and C by 2030 was evaluated and reported. Collected data shows that countries have made significant efforts toward achieving goals in the Global Health Sector Strategy. All countries have national programs focused on hepatitis elimination and have reached the target vaccination coverage against hepatitis B. However, the available information requires regular updates, and public accessibility of data collected by governments should be enhanced. Additionally, countries are recommended to improve harm reduction and treatment services.